The risks of current political risk management - Bussotti, L. (Problems of Management in the 21st Century, 2014)
A new approach to the management of political risk is possible. If governors are perceived as “dangerous” by the governed, it means they are high risk: consequently, a science of political risk management directed towards the interests of MNCs and the local ruling class is a risk for the majority of people living in the developing countries.